Penerapan Algoritma SAGE pada Pengukuran Kanal Indoor Menggunakan SDR-USRP - Musayyanah Musayyanah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Cooperative Wireless Communications forming MIMO array of virtual communication systems, which can improve the speed of data transmission, the speed is affected by channel conditions, that required the technique of channel analysis. The channel can be identified by knowing the characteristics of the physical parameters of the channel, like delay, angle, and amplitude complex. Detection of the physical parameters, from measurement of indoor or outdoor channel should use some methods with high accuracy, such as Space Alternate Generalized Expectation Maximization (SAGE). In this paper, we discuss the application of SAGE, to detect the angle parameters consists of Direction of Arrival (DoA) and the Direction of Departure (DoD), uses a communication device, Software Define Radio (SDR) such as Universal Software Radio Peripheral (USRP) that can detect three signals from measuring the indoor channel. The results of SAGE are compared with the results of Ray Tracing, where the average error for DoD detection was 36.3% while the DoA approximately 29.3%